The nucleic acid reactions on the nanomaterials surface for biomedicine - Zhenrui Xue; Lu Wang; Shengnan Pan; Jie Yan; Minli You; Chunyan Yao (Journal of Nanobiotechnology)
Abstract Integrating nucleic acids (NAs) with nanomaterials has substantially advanced biomedical research, enabling critical applications in biosensing, drug delivery, therapeutics, and the synthesis of nanomaterials. At the core of these advances are the reactions of NAs on nanomaterial surfaces, encompassing conjugation (covalent and non-covalent), detachment (physical and chemical), and signal amplification (enzyme-mediated signal amplification, enzyme-free signal amplification, and DNA Walker). Here, we review the fundamental mechanisms and recent progress in nucleic acid reactions on nanomaterial surfaces, discuss emerging applications for diagnostics, nanomedicine, and gene therapy, and explore persistent challenges in the field. We offer a forward-looking perspective on how future developments could better control, optimize, and harness these reactions for transformative advances in nanomedicine and biomedical engineering. Graphical abstract